2022
DOI: 10.1111/1754-9485.13374
|View full text |Cite
|
Sign up to set email alerts
|

Plan quality in radiotherapy treatment planning – Review of the factors and challenges

Abstract: A high-quality treatment plan aims to best achieve the clinical prescription, balancing high target dose to maximise tumour control against sufficiently low organ-at-risk dose for acceptably low toxicity. Treatment planning (TP) includes multiple steps from simulation/imaging and segmentation to technical plan production and reporting. Consistent quality across this process requires close collaboration and communication between clinical and technical experts, to clearly understand clinical requirements and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 114 publications
1
7
0
1
Order By: Relevance
“…The hybrid planning performed significantly better than manual planning in OAR sparing (Additional file 1: Table S1), except for left femur head D 25 , which showed no significant difference. This result is similar to the conclusion proposed by Hansen et al [22], who concluded that, on average, automated planning reduces the OAR dose compared to manual planning.…”
Section: Discussionsupporting
confidence: 91%
“…The hybrid planning performed significantly better than manual planning in OAR sparing (Additional file 1: Table S1), except for left femur head D 25 , which showed no significant difference. This result is similar to the conclusion proposed by Hansen et al [22], who concluded that, on average, automated planning reduces the OAR dose compared to manual planning.…”
Section: Discussionsupporting
confidence: 91%
“…It is also important to note that the quality of treatment delivery is intrinsically linked to other upstream activities such as treatment planning and simulation which are covered in a separate article in the present special issue of JMIRO 29 …”
Section: Treatment Delivery: Technology and Techniquesmentioning
confidence: 99%
“…It is also important to note that the quality of treatment delivery is intrinsically linked to other upstream activities such as treatment planning and simulation which are covered in a separate article in the present special issue of JMIRO. 29 A system to ensure fitness of purpose for radiotherapy delivery equipment Quality considerations for equipment used for patient treatment can be associated with a few distinct activities…”
Section: Risk Managementmentioning
confidence: 99%
“…Once a treatment plan is created, the next important step in the radiotherapy workflow is to evaluate the plan quality to determine if it is clinically acceptable and safe [3,4]. The quality of a plan is evaluated using several qualitative and quantitative metrics [2,3].…”
Section: Introductionmentioning
confidence: 99%